Homo Ridens: Suatu Tawaran ‘Menjadi’ Manusia di Zaman Ini - Priyambodo, Yulius Eko (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
Human forgets, but at the same time longs for one of the basic hopes that might disclose the web of meanings within the world of human existence. One might start asking about one’s fundamental reasons to exist, and one of them is to use language. Still, language is understood and used in multifaceted ways. In these miscellaneous interpretations of language, one that is quite seldom to explore is human language to express humour. Humour entails laugh and joy, and these bring forth nothing less than happiness that seem to have been eternally carved in the history of humankind. Reflecting on this aspect of language, this article wants to explore the human as homo ridens, a laughing being, which foreseeably brings forward his/her dimensions as a playful being, a social being, and a spiritual being. The author tries to show the relevance of a laughing human with the struggle of every individual to be a more authentic, social, and faithful person.